All-a-glow: spectral characteristics confirm widespread fluorescence for mammals - Travouillon, Kenny J.; Cooper, Christine; Bouzin, Jemmy T.; Umbrello, L.S.; Lewis, Simon (Royal Society, 2023)
Mammalian fluorescence has been reported from numerous species of monotreme, marsupial and placental mammal. However, it is unknown how widespread this phenomenon is among mammals, it is unclear for many species if these observations of ‘glowing’ are true fluorescence and the biological function of fluorescence remains undetermined. We examined a wide range of mammal species held in a museum collection for the presence of apparent fluorescence using UV light, and then analysed a subset of preserved and non-preserved specimens by fluorescent spectroscopy at three different excitation wavelengths to assess whether the observations were fluorescence or optical scatter, and the impact of specimen preservation. We also evaluated if fluorescence was related to biological traits. We found that fluorescence is widespread in mammalian taxa; we identified examples of the phenomena among 125 species representing all 27 living mammalian orders and 79 families. For a number of model species, there was no evidence of a corresponding shift in the emission spectra when the wavelength of excitation was shifted, suggesting that observations of ‘glowing’ mammals were indeed fluorescence. Preservation method impacted the intensity of fluorescence. Fluorescence was most common and most intense among nocturnal species and those with terrestrial, arboreal and fossorial habits, with more of their body being more fluorescent. It remains unclear if fluorescence has any specific biological role for mammals. It appears to be a ubiquitous property of unpigmented fur and skin but may function to make these areas appear brighter and therefore enhance visual signalling, especially for nocturnal species.